Acute Renal Failure due to Obstructive Uropathy Secondary to Ureteral Endometriosis - Jeong In Choi; Jee Geun Yoo; Sa Jin Kim; Hae Nam Lee; Min Jeong Kim (Case Reports in Obstetrics and Gynecology)
Ureteral involvement by endometriosis is a rare and often silent disease but capable of producing significant morbidity and leading to hydronephrosis and to renal failure. Surgery is the treatment of choice to remove endometriotic lesions and relieve ureteral obstruction if the kidney is still functional or a nephrectomy is performed if there is a complete loss of renal function. We report a case of acute renal failure induced ureteral endometriosis managed with laparoscopic unilateral nephrectomy and endometrioma cystectomy. Differential diagnosis is important to confirm diagnosis for patients with ureteral obstruction presenting nonspecific symptoms.